Membangun Kemandirian Ekonomi Santri: Optimalisasi Literasi dan Hukum Syariah dalam Praktik Kewirausahaan di Pesantren - Muhsyanur, Muhsyanur; Hasriadi, Hasriadi; Danil, Harling; Rahmi, Muarifah; Amiruddin, Ahmad Rijal; Wahyuni, Sri; Wafiyah, Ummul; Arsyad, Ahmad Yamani; Amiruddin, Amiruddin; Sapri, Hasri Amaliah; Harianti, Harianti; Hasbi, Muhammad; Nur, Muh. Yasin Ceh (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
This community service research aims to empower santri at the As'adiyah Islamic Boarding School Lapai Branch through an integrative approach that synergizes Indonesian language literacy, Islamic economic law, character education, and entrepreneurship. The implementation method uses a participatory approach with stages of preparation, needs identification, collaborative planning, scientific aspect integration, and student bazaar implementation. Results show significant improvements in santri capabilities, with 18 out of 25 business groups achieving sales targets. Program impacts include institutional transformation of the pesantren, improved literacy, understanding of Islamic economics, and Islamic character formation. The research conclusion affirms the effectiveness of a holistic approach in empowering santri and the potential of pesantren as an adaptive educational institution.